Identifikasi Kerentanan Longsor Daerah Pangalengan Dengan Metode Slope Morphology - R. Amukti; D. Mildan; I. A. Dinata; N. F. Isniarno; I. K. Wijaksana (Universitas Negeri Malang, 2017)
Pangalengan is located between 107o29'-107o39 'BT and 7o19'-7o6' LS. Based on its topography and geological condition, Pangalengan has steep slopes and lies between two strike-slip faults. Average annual rainfall of this area is about 1,996 mm with 5.47 mm of average daily rainfall. The area is about 27294.79 hectares with population of 148353 inhabitants. According to these data, Pangalengan has high risk of landslide. Landslide occurred in Pangalengan on 05-05-2015 at 14:00 pm, caused 9 fatalities, 4 people seriously injured, 134 people evacuated, 10 houses buried, geothermal steam flow pipe of Energy Star damaged. It is necessary to analyze slope morphology and study the potential hazard areas of landslide. The result shows that Cibitung which has steep (35o-45o) and very steep (45o-65o) slope is prone to landslide with an area of ± 3038 hectares spread to the south.DOI: http://dx.doi.org/10.17977/um024v2i12017p001